Resposta :
Resposta:
Resposta [tex]a=\sqrt{3}[/tex]
Explicação passo a passo:
Lei dos cossenos:
[tex]a^{2}=b^{2}+c^{2} - 2\cdot b\cdot c\cdot \cos{30}\\a^{2}=(2\sqrt{3})^{2}+3^{2}-2\cdot (2\sqrt{3})\cdot 3\cdot \frac{\sqrt{3}}{2}\\a^{2}=4\cdot 3+9-(6\cdot3)\\a^{2}=3\\a=\sqrt{3}[/tex]
Resposta:
a = √3
Explicação passo a passo:
∝ = 30°
b = 2√3
c = 3
a = ?
Lei dos Cossenos:
a² = b² + c² - 2 . b . c . cos ∝
a² = (2√3)² + 3² - 2 . 2√3 . 3 . cos 30°
a² = 4 . 3 + 9 - 12√3 . √3 / 2
a² = 12 + 9 - 12 . 3 / 2
a² = 21 - 36 / 2
a² = 21 - 18
a² = 3